Геоінформатика: історія становлення, предмет, метод, задачі (сучасна точка зору). Стаття XXVI - Кулінкович, А.Є.; Якимчук, М.А. (Центр менеджменту та маркетингу в галузі наук про Землю ІГН НАН України, 2008)
В настоящей, двадцать шестой статье данной серии анализируется выполнение двух мегапрограмм – «мегапрограммы Физики» и «мегапрограммы Информатики». Исполнение этих мегапрограмм завершилось разработкой концепции «Вселенная – это организм, развивающийся в соответствии с управляющей информацией, порождаемой вселенским музыкально-фрактальным календарем». In the twenty-sixth paper of the given series of papers there is analyzes the realization of two megaprogrammes – “the megaprogramme of Physics” and “megaprogramme of Informatics”. The fulfilment of these megaprogrammes was completed by the creation of the concept “the Universe is an organism that develops in accordance with controlling information. This information is engendered by the universal musical fractal calendar”.